1998
DOI: 10.1177/089686089801800412
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Chronic Peritoneal Dialysis Catheter

Abstract: Background Damage to the peritoneal dialysis catheter may be due to wear from long-term use, exposure to antibacterial agents (strong oxidants), and accidental injury from sharp objects. Repair of such catheter, if not associated with subsequent complications, would extend catheter life and reduce costs and patient inconvenience related to catheter replacement. Objective and Design Retrospective analysis of seven peritoneal catheters repaired 11 times over a 15-year period by splicing the old catheter with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Damage to the external catheter tubing may result from sharp instrument cuts or punctures, fracture from crushing clamps, catheter adapter tears, or chemical destruction of the catheter material from antibiotic ointments or organic solvents. External splicing repair by the PD nursing staff using commercially available repair kits is possible if at least 2 cm of tubing is present beyond the exit site (185). Catheter damage with leak is considered a contaminating event, and investigation for peritonitis is required and prophylactic antibiotics indicated.…”
Section: External Catheter Damagementioning
confidence: 99%
“…Damage to the external catheter tubing may result from sharp instrument cuts or punctures, fracture from crushing clamps, catheter adapter tears, or chemical destruction of the catheter material from antibiotic ointments or organic solvents. External splicing repair by the PD nursing staff using commercially available repair kits is possible if at least 2 cm of tubing is present beyond the exit site (185). Catheter damage with leak is considered a contaminating event, and investigation for peritonitis is required and prophylactic antibiotics indicated.…”
Section: External Catheter Damagementioning
confidence: 99%
“…However, these problems may be significantly attenuated by the replacement of a significant part of the catheter segment including a new external cuff. Previous studies presented methods for replacement of the catheter segment 12–14 . Asif et al reported a catheter repair method using a connector, while another study showed replacement of catheter segment using a beta‐cap adapter from a PD catheter set 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…The PD catheter was maintained without complications for the next 6 months between post‐operation and the time of last outpatient department visit. Many practitioners may plan removal of the original catheter and reinsertion of a new PD catheter in the absence of a kit for repair of the PD catheter 2 . Our case shows that repair of the PD catheter using this manipulated material may be helpful to salvage intramural and internal segments without an additional repair kit for a PD catheter ruptured in its external segment.…”
Section: Figurementioning
confidence: 91%